2020
DOI: 10.1007/s40415-020-00639-y
|View full text |Cite
|
Sign up to set email alerts
|

Sargassum stenophyllum (Fucales, Ochrophyta) responses to temperature short-term exposure: photosynthesis and chemical composition

Abstract: Sargassum species form extensive benthic beds in tropical and subtropical low intertidal and subtidal zones, acting as important drivers for marine community structure. Temperature, as one of the most important abiotic factor, affects seaweed performance and triggers changes in metabolic responses; therefore, laboratory experiments involving temperature ranges are tools for understanding seaweed engineering. The aim of this study was to assess the physiological vulnerability and sensitivity of Sargassum stenop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 71 publications
1
1
0
Order By: Relevance
“…The respiration rates we measured exponentially increased with the temperature as it was shown in other seaweed species (Piñeiro-Corbeira et al, 2018;Dıáz-acosta et al, 2021) and it could indicate a possible shift towards heterotrophic metabolism (Brown et al, 2004;Bennett et al, 2022b). Studies conducted on other representatives of the order Fucales showed marked signs of tissue necrosis at higher temperatures (Flukes et al, 2015;Graiff et al, 2015;Urrea-Victoria et al, 2020). Similarly, the high respiration rate we recorded at 35°C (Figure 4C) is likely to be the result of microbial community activity associated to the decaying seaweed, as indicated by G. rayssiae's discoloration, tissue necrosis and deterioration at these higher temperatures (Supplementary Figure S8).…”
Section: Thermal Vulnerabilitysupporting
confidence: 60%
“…The respiration rates we measured exponentially increased with the temperature as it was shown in other seaweed species (Piñeiro-Corbeira et al, 2018;Dıáz-acosta et al, 2021) and it could indicate a possible shift towards heterotrophic metabolism (Brown et al, 2004;Bennett et al, 2022b). Studies conducted on other representatives of the order Fucales showed marked signs of tissue necrosis at higher temperatures (Flukes et al, 2015;Graiff et al, 2015;Urrea-Victoria et al, 2020). Similarly, the high respiration rate we recorded at 35°C (Figure 4C) is likely to be the result of microbial community activity associated to the decaying seaweed, as indicated by G. rayssiae's discoloration, tissue necrosis and deterioration at these higher temperatures (Supplementary Figure S8).…”
Section: Thermal Vulnerabilitysupporting
confidence: 60%
“…Lessonia flavicans, L. nigrescens, and L. trabeculata extracts provide a mixture of fucans and alginic acid that may be applied in agriculture as a pesticide against harmful fungi in wheat and tobacco (Percival et al 1983;Chandía et al 2004Chandía et al , 2005Matsuhiro and Zambrano 2004). Fucoidan and alginic acid compositions are altered depending on the environmental conditions to which the seaweeds are exposed (water motion, light and temperature) (Martins et al 2011;Valiente and Mogollón 2013;Harb et al 2018;Urrea-Victoria et al 2020). For example, Lessonia from exposed sites produces a high content of polysaccharides compared to sheltered sites, in addition to different gel quality throughout the year (Chandía et al 2004(Chandía et al , 2005Valiente and Mogollón 2013;Leal et al 2018;Zou et al 2019).…”
Section: Commercial Applications Of Lessonia Sppmentioning
confidence: 99%